Cato's letters - Trenchard, John ((The Eighteenth Century ; reel 5993, no. 01)., 1723)
"First published weekly in the London and British journals ... Written without any name, from Bath, as letters to the author of the London journal, who ... sign'd them Cato, and by that name they aferwards went."--Pref.